The role of mass media in shaping the image of a political leader on the example of the President of the Republic of Uzbekistan Sh. Mirziyoyev (Herald of Journalism, 2022)
This article analyzes media messages regarding the activities of the second president of the Republic of Uzbekistan Shavkat Mirziyoyev. An assessment is made on the formation and transformation of the president's image based on scientific literature on this topic and media content. The methodological base is the study of materials of famous scientists, as well as media reports to review and analyze the development of the image of the president of Uzbekistan from 2016 to 2022.The purpose of the study is to determine the type of image of the head of state, formed with the help of the media, as well as the process of its change and evolution from the time of election to the present period. The activity of the president in the context of providing informational occasions and the subsequent influence of Uzbek and other media of various directions and genres on the formation of the image are studied. The role of the mass media in the design and promotion of the image of the head of state is critically analyzed on the example of Sh. Mirziyoyev, both among the citizens of the state and citizens of other states. The article also traces the connection between the image of Sh. Mirziyoyev as a president and the brand image of the Republic of Uzbekistan.The results of the work can be considered confirmation of the close relationship between the media and the formation of the image of the head of state, while informational occasions, including those that have a secondary effect on the development of the image of the head of state in close dependence on the image of the state as a whole, can also be created by the president himself. The importance of forming certain types of positive image of the head of state in connection with the design of an open and positive brand of the state is traced.The relevance of the study of media interaction and the work of the head of state to form a positive image is confirmed by the need to ensure citizens' confidence in the policy of their leader, increase his authority and voter loyalty, and, as a result, establish a positive image of the state in the international arena.Keywords: president, Republic of Uzbekistan, image, media, Sh. Mirziyoev, reforms.